Use of bone marrow for detection of toxic chemicals for the elucidation of poisoning in forensic veterinary medicine - Sóstenes A.C. Marcelino; Rogéria Serakides; Viviane N. Castro-Silva; Maria L. Ramos; Natália M. Ocarino; Marília M. Melo (Pesquisa Veterinária Brasileira, 2020)
ABSTRACT: In forensic toxicology, the detection of toxic chemicals from human bone marrow is often used in cases with an extended post mortem interval; however, in veterinary medicine, this practice is not used. Therefore, this study was performed to investigate the suitability of bone marrow for toxicological analysis in dogs and cats. Six animals with suspected poisoning were selected; the carcasses were sent for necropsy, and the organs were collected and preserved in buffered formalin and processed routinely for histological examination. In addition, bone marrow samples from the femur, humerus, and tibia were collected for toxicological analysis by liquid chromatography coupled to mass spectrometry detection (LC-MS). This analysis confirmed the presence of aldicarb, aldicarb sulfone, asulam, carbendazim, chlorpyrifos, dichlorvos, thifensulfuron methyl and trifloxysulfuron-sodium and associated with clinical symptoms and anatomo-histopathological alterations it was recognized the poisonings. It is expected that this study will promote the toxicological investigation of bone marrow and open avenues for the use of this tissue as an option for the detection of toxic chemicals in cases of forensic pathology.